Rotor Failure Diagnosis of Induction Motors by Wavelet Transform and Fourier Transform in Function of the Load - Costa, Cesar da; Kashiwagi, Masamori [UNESP]; Mathias, Mauro Hugo [UNESP] (Destech Publications, Inc, 2015)
This paper presents two diagnostic methods for the online detection of broken bars in induction motors with squirrel-cage type rotors. The wavelet representation of a function is a new technique. Wavelet transform of a function is the improved version of Fourier transform. Fourier transform is a powerful tool for analyzing the components of a stationary signal. But it is failed for analyzing the non-stationary signal whereas wavelet transform allows the components of a non-stationary signal to be analyzed. In this paper, our main goal is to find out the advantages of wavelet transform compared to Fourier transform in rotor failure diagnosis of induction motors.
Keywords: Rotating electrical machine; Diagnostic; Digital signal processing